Sexuality Education for Early Childhood: Themes, Methods, and Perceptions of Raudhatul Athfal (RA) Educators - Hardiyanti Pratiwi; Murniyanti Ismail; Rizky Noor Haida (Badan Standar, Kurikulum, dan Asesmen Pendidikan, Kemendikdasmen, 2023)
Sexuality education equips children with knowledge about the functions of genital organs, help them maintain hygiene, and protect themselves from sexual violence. This study aims to investigate the themes, methods, and perceptions of educators regarding sexuality education. The research utilized a quantitative survey involving 247 educators. An online questionnaire with both closed and open-ended questions was employed as the research instrument, and the data were analyzed using descriptive statistical methods for closed questions and qualitative methods for open-ended questions. The content validity of the instrument was established through validation by psychologists, indicating that the questionnaire could be effectively used. The reliability of the instrument was assessed using Cronbach’s Alpha. The results indicated that the majority of respondents emphasized the importance of introducing sexuality education at an early stage. However, the lack of knowledge regarding suitable themes, limited teaching materials, and negative societal stigma were identified as significant challenges. Despite these obstacles, respondents acknowledged the importance of teaching various themes, such as protecting sensitive areas, maintaining the health and hygiene of genital organs, addressing religious norms related to interactions with the opposite sex, and respecting the privacy of others. Respondents suggested that the most effective methods for introducing these themes included the use of songs, fairy tales, and role-playing activities. The pedagogical implication of this study underscores the need to enhance educators’ knowledge about sexuality education and provide them with adequate teaching materials.